Effect of environmental temperature and relative humidity towards postural behavior and activity patterns of female Pongo pygmaeus at Bukit Merah Orang Utan Island, Perak, Malaysia (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Nozmi N, Dharmalingam S, Yusof NNM, Yusof FZM. 2023. Effect of environmental temperature and relative humidity towards postural behavior and activity patterns of female Pongo pygmaeus at Bukit Merah Orang Utan Island, Perak, Malaysia. Biodiversitas 24: 1252-1263. Variation in environmental conditions is known to have impacts on animal behavior. Previous research showed animals adapt to temperature change by altering their behavior and routine or resorting to relocation in order to survive. This study aims to determine the strength of the correlation between the environmental conditions with Bornean orangutans (Pongo pygmaeus) postural behavior and activity patterns in captivity. Focal sampling was carried out at Bukit Merah Orang Utan Island, Perak, Malaysia, for 93 days from March 2021 until June 2021 among four adult female orangutans. Four postural behaviors were observed, which are sitting, lying, clinging and standing, and four activities were selected, which are resting, feeding, playing and moving. We used RS PRO DT-3893 Vane Anemometer to determine the environmental temperature and relative humidity. The data were analyzed via Mann-Whitney U-test. Orangutans had a longer resting period (p: 0.023) and a lying period (p: 0.002) at high temperatures. The behavioral observation also shows similar findings in resting (p: 0.015) and lying duration (p: 0.001) in lower humidity. The results of this study will enhance our understanding of the behavior pattern of female orangutans in ensuring the effectiveness of enrichment activities in the future. This study will also serve as baseline data of behavioral patterns in response to variations of environmental conditions which is affecting the behavior of orangutans in captivity.
Keywords: Activity budget, ambient temperature, environmental humidity, female orangutan, postural modes